A study on risk factors and lipid profile pattern in patients of stroke in Osmania General Hospital, Hyderabad, India - Siddeswari, Ravala; Sudarsi, Budithi; Abhilash, Thatikala; Rao, Nanyam Srinivasa (International Journal of Research in Medical Sciences, 2017)
Background: Aim of current study was to study the risk factors and dyslipidemia in 100 patients of stroke admitted in Osmania General Hospital. Methods: This was a retrospective descriptive study, which included 100 patients of both ischemic and haemorrhagic strokes who were admitted in Osmania General Hospital. Patients on lipid lowering therapy were excluded from study. History of risk factors like hypertension, diabetes, alcohol and smoking were taken. To determine the subtype of stroke, clinical examination followed by computed tomography scan of brain was done. A serum sample after 8 hours of overnight fasting was taken and total serum cholesterol (TC), triglycerides (TG), LDL-cholesterol, VLDL-cholesterol and HDL-cholesterol was determined, using enzymatic colorimetric method. Results: A total of 100 patients were studied. There were 72 males & 28 females. Patients with age <40 years were 4, age between 40-60 years were 63 and age >60 years were 33, with a mean age of 57.6 ± 12.15. Out of 100 patients, 82 had ischemic stroke & 18 had hemorrhagic stroke. In this study, patients with high LDL were 21, with mean LDL of 93.28 ± 38.26, high total cholesterol were 20, with a mean of 151.73 ± 47.65, low HDL cholesterol in 66, with mean of 35.29 ± 11.26, high triglycerides in 8, with a mean of 119.43 ± 58.09. Dyslipidemia (LDL>130; TC>200; HDL<40) as per ATP III guidelines was present in 14 patients. Among 100 patients 65 had hypertension, 23 had diabetes, 15 had both diabetics and hypertension, 39 were smokers, 39 consumed alcohol and >2 risk factors were found in 23. There were 6 deaths. Conclusions: In the present study common risk factors observed were male sex, mean age of 40-60 years and hypertension. Dyslipidemia as per ATP III guidelines was present in 14% of stroke patients. Most of the patients were having low HDL (<40 mg/dL) which is a risk factor for stroke. This study enlightens the role of HDL in development of stroke which is having a protective role in preventing stroke.